The Influence of Providing Information and Educational Media in Efforts to Prevent Stroke - Wijaya, Cindy Eka; Pratama, Irza Haicha; Girsang, Ermi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Stroke is the leading cause of physical and mental disability worldwide. In Indonesia, the incidence of stroke is alarmingly high, affecting approximately 10.9% of the population annually, with around 713,783 individuals experiencing stroke each year. Understanding how to prevent stroke is crucial. Clear and regular information, along with effective educational media, are essential for increasing public awareness of stroke. This study aims to determine the impact of social media and knowledge on stroke prevention. This type of study is a non-experimental quantitative study using a cross-sectional. This study is conducted in portions, with patients who are willing and able to talk effectively. Univariate, bivariate, and multivariate analyses were conducted using Pearson correlation tests and linear regression tests. The results show that among the 100 respondents, most were male, aged 41-60 years, and engaged in the best stroke prevention efforts. The Pearson correlation test showed significant correlations between information accuracy, frequency, and educational media for stroke prevention (Pearson p=0.89; p=0.62; p=0.75). The linear regression test revealed that the clarity of information, frequency of information, and educational media together increased stroke prevention efforts (p=0.037), with the clarity of information being the most significant factor. The conclusion is the study concludes that educational media and accurate information are crucial in preventing stroke. It is recommended that the Kasih Sayang Clinic conducts comprehensive stroke education and screening every six months to enhance prevention efforts.